Consciousness as creative force and prison cell in Nabokov's "Mademoiselle O" - Neumann, Claus-Peter (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2004)
Published in five essentially different versions, on some occasions as short story, on others as part of his autobiography, Nabokov’s “Mademoiselle O” challenges the boundaries between the two genres. An analysis of how plot, titular character and narrative voice relate to each other in the 1947 version, published in identical form both as independent short story and as chapter of the memoir Conclusive Evidence, yields insights into Nabokov’s conception of the interrelation between memory and imagination. In this conception human consciousness reveals itself as a conditioning force acting on memory, suggesting the ontological impossibility of all autobiography. However, tensions created by textual passages that provide a contrast to the narrator’s version of events insinuate that consciousness has its limits, thus showing a way of saving memory from fiction, albeit on a subliminal level that undermines the narrative voice itself.